Lasius fuliginosus - Collingwood, C. A. (Zenodo, 1979)
37. Lasius fuliginosus (Latreille, 1798) Figs. 136-138. Formica fuliginosa Latreille, 1798:36. Worker. Shining black, legs brownish yellow; pubescence sparse, scattered erect hairs over dorsum. Head broadly cordate, emarginate posteriorly with rounded occipital lobes; genital margins incurving towards mandibular insertions. Maxillary palps short with segments 4, 5 and 6 subequal. Petiole thickened wedge shaped in profile, with feebly convex faces, dorsal margin narrow, convex or straight. Length: 4.0-6.0 mm. Queen. Colour and shape as worker. Pubescence and body hairs thicker and more abundant than worker. Head width: 1.45-1.65 mm, broader than alitrunk. Length: 6.0-6.5 mm. Male. Shining black; head cordate, not emarginate posteriorly, as wide as alitrunk. Petiole low and thick with rounded dorsal margin. Mandibles with apical tooth only. Length: 4.5-5.0 mm. Distribution. Throughout Denmark and Southern Fennoscandia to latitude 62°; South Ireland, England and Wales. - Range: Portugal to Japan and North India, South Italy to Finland. Biology. This distinctive species is easily recognised by its shining black colour and broad head. Carton nests are constructed at the base of old trees, hedgerows and sometimes in sand dunes and in old walls. Colonies are populous, often polycalic with more than one focal nest and several queens. Workers forage above ground in narrow files throughout the day and night during warm weather, ascending trees and shrubs to tend aphids. The mandibles are relatively weak but small insects may be taken as food. Other competing ant species are repelled by aromatic anal secretions. Fertilised queens may be retained in the old nest or found fresh colonies through adoption by the members of the Lasius umbratus species group; mixed colonies with L. umbratus or L. mixtus have often been observed. Flight periods are irregular and have been recorded in all months from May to October. A number of local beetles occur with this species including members of the genus Zyras which exhibit protective mimicry. Walden (1964), records an enormous nest measuring 63 x 55 x 55 cm found in a cellar near Goteborg and there are similar reports from outbuildings and cellars in England (Donisthorpe, 1927). : Published as part of Collingwood, C. A., 1979, The Formicidae (Hymenoptera) of Fennoscandia and Denmark., pp. 1-174 in Fauna Entomologica Scandinavica 8 on pages 100-101